Policy Implementation of Mayor Regulation Number 21 of 2020 concerning the Implementation of an Integrated Public Safety Service Center in Padang, West Sumatera, Indonesia - Irwan, Viola Fathia; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Public service is an important element in improving the quality of life in the community. The government plays an important role in providing public services, especially in the emergency department. This study aims to analyze the implementation of the Padang mayor's regulation number 21 of 2020 regarding the implementation of an integrated safety service center in the city of Padang.Subjects and Method: This was a descriptive qualitative study. The study was conducted in Padang, West Sumatera, Indonesia, from April 18 to May 31, 2022. The primary data were obtained directly through interviews with selected informants. Results: The Policy Implications of the Padang Mayor's Regulation Number 21 of 2020 concerning the Implementation of an Integrated Safety Service Center (Public Safety Center) in the City of Padang is based on the Regulation of the Minister of Health of the Republic of Indonesia Number 19 of 2016 concerning the Integrated Emergency Management System. In its implementation, the Padang City Health Office still relies on health workers at the Puskesmas because PSC 119 does not yet have its own special team or officers. The Padang City Health Office has not officially disseminated to the public and has not officially collaborated with external parties.Conclusion: The policy of Padang Mayor Regulation Number 21 of 2020 as a whole is the authority and responsibility of the Padang City Health Office. The Padang City Health Office has not officially disseminated to the public and has not officially collaborated with external parties. In its implementation, the Padang City Health Office still relies on health workers at the Puskesmas because PSC 119 does not yet have its own special team or officers.Keywords: Policy Implementation, PSC 119, Integrated Service Center.Correspondence: Viola Fathia Irwan. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: violairwan@gmail.com. Mobile: +6281270403409.Journal of Health Policy and Management, (2022), 07(02): 139-148https://doi.org/10.26911/thejhpm.2022.07.02.05.